2020
DOI: 10.1007/s40520-020-01573-5
|View full text |Cite
|
Sign up to set email alerts
|

A National Multicenter Study on overall survival in elderly metastatic castrate-resistant prostate cancer patients treated with Radium-223

Abstract: Background Radium-223 prolongs overall survival (OS) and delays time to the first symptomatic skeletal events in patients with symptomatic metastatic castration-resistant prostate cancer (mCRPC). There is a lack of evidence on the safety and efficacy of Radium-223 treatment in the very elderly population. Aims Aim of this multicentre study is to analyze mCRPC patients treated with Radium-223 in terms of OS and to assess whether there are differences between young and elderly, as well as to verify efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Some of the baseline characteristics known to be potential keys to radium-233 treatment success are PSA, ECOG performance status, pain status, baseline tALP, and Hb ( 9 , 18 , 25 ) . Frantellizzi et al ( 26 ) found no differences between responders and nonresponders in terms of age and baseline characteristics, although they found that a three-variable score could be a useful predictor of treatment success. They showed that patients with an ECOG performance status of 0 or 1, PSA < 20 ng/mL, and Hb > 12 g/dL were likely to show a better response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the baseline characteristics known to be potential keys to radium-233 treatment success are PSA, ECOG performance status, pain status, baseline tALP, and Hb ( 9 , 18 , 25 ) . Frantellizzi et al ( 26 ) found no differences between responders and nonresponders in terms of age and baseline characteristics, although they found that a three-variable score could be a useful predictor of treatment success. They showed that patients with an ECOG performance status of 0 or 1, PSA < 20 ng/mL, and Hb > 12 g/dL were likely to show a better response.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of other characteristics, a greater number of cycles of treatment is consider one of the main predictors of prolonged OS (18,(25)(26)(27)(28) . In the present study, OS was significantly longer among the patients receiving five or six cycles of radium-223 therapy than among those receiving fewer cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The cited work was obtained on the same population sample of this study, however the purpose and results obtained are totally different and have not been duplicated in any way. In fact, while the manuscript presented (3-PS) focuses on the statistical validation of a multidimensional system that allows the better selection of patients who can benefit from 223 Ra in terms of OS, the previous article published in a geriatric journal, analyzed the population based on age and therefore took into account efficacy, toxicity profiles and survival in elderly patients [20].…”
Section: Toxicitymentioning
confidence: 99%
“…It is important to note that osteoporotic acetabular fractures might be managed following different surgical principles, compared to the high-energy fractures observed in young patients. Moreover, it could be difficult to achieve the anatomical reduction and stable fixation of osteoporotic QP fractures, because of the QP location in the true pelvis and juxta-articular position, the frequent fracture comminution and the poor bone quality [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%